Marketing Strategy of Alteregos Custom Made T-Shirt Created Upon Customer Characters - Hadiwijaya, Nugraha; Larso, Dwi (The Indonesian Journal of Business Administration, 2014)
Abstract.Nowadays, a product is not always valued from its function, but has expanded to intrinsic value which nowadays it is about uniqueness. ALTEREGOS offers its product; manually painted T-Shirt, that each painted design are customer characters, so that a customer will receive one design. According to a survey to 75 respondent, author gained an information that product which offered by ALTEREGOS has not exist yet, or the respondent has never heard before.The problem comes from the customer`s awareness to the product that offered by ALTEREGOS. To the purpose of gaining awareness from customers, ALTEREGOS maximizes the power of marketing to social media, especially Facebook and Instagram, as the medium of low-cost marketing. These two social media are compatible to commit marketing activities, as these two are excellent visually, and for they who have narcissistic side, these two social media are promising self-actualization visually. Furthermore, in every year we will hold annual exhibition which displaying ALTEREGOS product, in order to increase brand awareness. Solutions are found by using qualitative method, through analysis and comparative case study by porter five forces and PEST. An appropriate marketing strategy is an important starting point to increase brand awareness so the product life span will long lasting and become a sustainable business.Key Words: Creative Industry, Clothing, Marketing Strategy.Â